Constructing identities in late antiquity - Miles, Richard, 1969- (Routledge, 1999)
Examines the theme of identity: geographic, ethnic, religious, status and sex-based. Discussions of Roman texts and images show how constructions of identity and culture contributed to the creation of late antiquity" as a historical concept."